Development of creative abilities among preschoolers in art-aesthetic activity - Chumakova I. V., Svistunova E. G. (Pedagogical excellence and pedagogical technologies, 2016)
the article considers the problems of development of creative abilities of preschool children in artistic and aesthetic activitiy based on diagnostic data and the system of selection of developmental tasks for solving creative abilities activation among preschool children and education of a harmonious personality.
Keywords: дети; личностно-ориентированный подход; педагогическая диагностика; формирование творческой личности; children; творческая индивидуальность; активизация творческих способностей; художественно-практическая деятельность; personality-oriented approach; pedagogical diagnostics; formation of a creative personality; creative personality; activation of creative abilities; artistic and practic activity